Casuística de consulta veterinaria en la clínica equina bejucal (2023)
The present work was based on a theoretical-practical experience in the field of clinical equine medicine, through an internship as a grade III work option, at the Bejucal Clinic, in the municipality of Cajicá, Cundinamarca, where mainly Basic aspects of care, hospitalization, post-operative care, some basic procedures that were usually performed in order to find a diagnosis, as well as some parameters for carrying out a satisfactory history, catamnesis and physical examination are described